2015
DOI: 10.1159/000370096
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Consolidative Radiotherapy after a Complete Response to Chemotherapy in the Treatment of Diffuse Large B-Cell Lymphoma in the Rituximab Era: Results from a Systematic Review with a Meta-Analysis

Abstract: Background: The current standard therapy for patients with diffuse large B-cell lymphoma (DLBCL) is rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone (RCHOP). The role of radiotherapy (RT) after complete response (CR) to RCHOP in patients with DLBCL remains unclear. This systematic review with a meta-analysis is an attempt to evaluate this role. Methods: Studies that evaluated RT versus no-RT after CR to RCHOP for DLBCL patients were searched in databases. Hazard ratios (HR) with their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…2 Radiotherapy is used in the treatment of NHL to improve outcomes of DLBCL patients who achieved a complete response (CR) to RCHOP. 4 Radiotherapy is also used in treatment of complication of the disease such as in bone metastases. 5 Herein, we present the case of a primary splenic DLBCL patient who was treated with chemotherapy RCHOP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Radiotherapy is used in the treatment of NHL to improve outcomes of DLBCL patients who achieved a complete response (CR) to RCHOP. 4 Radiotherapy is also used in treatment of complication of the disease such as in bone metastases. 5 Herein, we present the case of a primary splenic DLBCL patient who was treated with chemotherapy RCHOP.…”
Section: Introductionmentioning
confidence: 99%
“…4 Another systematic review with meta-analysis by Dos Santos et al, 12 showed that RT enhances progression free survival after chemotherapy with no impact on overall response rate and overall survival for aggressive and localized NHL. 12 Another role for radiotherapy consists of palliative treatment for bone metastases to relieve pain, preserve functions, and maintain skeletal integrity.…”
mentioning
confidence: 99%
“…In this issue of Acta Haematologica , Hu et al [1] present a systematic review and meta-analysis of recently published series comparing the role of 6-8 cycles of R-CHOP chemotherapy with or without the addition of consolidative radiotherapy for patients with diffuse large B cell lymphoma, stages I-IV. The authors queried MEDLINE, EMBASE and the Cochrane Library databases.…”
mentioning
confidence: 99%
“…Radiotherapy is listed as one of several options for bulky stage III/IV patients along with observation and transplant for high-risk patients after a complete response to 6 cycles of R-CHOP. As such, the use of radiotherapy varies highly from institution to institution, and the work of Hu et al [1] adds to the limited data regarding this issue [2], especially for stage III/IV patients where OS benefit may [3] or may not be evident. …”
mentioning
confidence: 99%
See 1 more Smart Citation